2012
DOI: 10.1371/journal.pone.0038752
|View full text |Cite
|
Sign up to set email alerts
|

Unique Responses of Stem Cell-Derived Vascular Endothelial and Mesenchymal Cells to High Levels of Glucose

Abstract: Diabetes leads to complications in selected organ systems, and vascular endothelial cell (EC) dysfunction and loss is the key initiating and perpetuating step in the development of these complications. Experimental and clinical studies have shown that hyperglycemia leads to EC dysfunction in diabetes. Vascular stem cells that give rise to endothelial progenitor cells (EPCs) and mesenchymal progenitor cells (MPCs) represent an attractive target for cell therapy for diabetic patients. Whether these vascular stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 38 publications
2
43
0
Order By: Relevance
“…Specifically, cell number was determined using Trypan blue dye exclusion assay and Scepter 2.0 Automated Cell Counter (Millipore) as previously described [47]. The colorimetric assay utilizing MTS reagent was used to establish the PIGA concentration that inhibited 50 % (IC 50 value) of U87MG cell survival after 24 h of treatment and was performed according to the manufacturer's instructions.…”
Section: U87mg Cells After Treatment: Survival Analysismentioning
confidence: 99%
“…Specifically, cell number was determined using Trypan blue dye exclusion assay and Scepter 2.0 Automated Cell Counter (Millipore) as previously described [47]. The colorimetric assay utilizing MTS reagent was used to establish the PIGA concentration that inhibited 50 % (IC 50 value) of U87MG cell survival after 24 h of treatment and was performed according to the manufacturer's instructions.…”
Section: U87mg Cells After Treatment: Survival Analysismentioning
confidence: 99%
“…31,36 These stem cells can be distinguished from hematopoietic stem cells by their ability to differentiate into endothelial and mural lineages and to regenerate functional vessels. 7,36,37 Studies have also shown that diabetes leads to reduced mobilization of stem cells from the marrow. 38,39 A number of signaling mechanisms have been identified underlying this abnormality.…”
Section: Diabetes and Its Complicationsmentioning
confidence: 99%
“…And finally, we have shown that high levels of glucose decrease endothelial and mesenchymal progenitor cell numbers acutely (within 24 h of culture). 37 However, cells recover from glucose toxicity with sustained exposure. In addition, the differentiation capacity of blood and bone marrow-derived stem cells to produce endothelial and mesenchymal progenitor cells is not altered by the presence of high levels of glucose.…”
Section: Diabetes and Its Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have shown that high glucose concentrations can impair original cellular functions such as apoptosis, viability and proliferation; besides, it can change the ability of primary cells in forming colonies in vitro and in vivo, regardless of their origin tissue (Li et al 2007). High glucose concentrations may also modify the gene expression and direct the differentiation of stem cells to the adipogenic over the chondrogenic and osteogenic lineages (Kearts & Khan 2012). On the other hand, glucose depletion improves these properties due to the overall beneficial effects already described of caloric restriction for stem cells, such as delay of cell death, senescence and ageing (Choudhery et al 2012).…”
Section: Bmmcs' Proliferationmentioning
confidence: 99%